Incorporating the Dimensions of Tolerance into Reading Materials-Development in Diverse EFL Classrooms - Aprianto, Dedi (SALEE: Study of Applied Linguistics and English Education, 2025)
This study addresses the challenges of teaching English as a Foreign Language (EFL) in diverse classrooms, emphasizing the need for materials that promote tolerance and inclusivity. It aims to fill a gap in existing curricula by developing reading materials that integrate tolerance dimensions, enhancing both language proficiency and socio-cultural understanding among EFL students. A mixed-methods approach was employed to provide practical insights and contribute to the theoretical framework of multicultural education in EFL contexts. The findings revealed that the experimental group, using the developed materials, achieved significantly higher scores (M = 85.6) compared to the control group (M = 78.2). An independent samples t-test confirmed a significant difference between the groups [t (84) = 20.777, p < 0.05], demonstrating the effectiveness of the materials in fostering student engagement and understanding of diverse perspectives. The study highlights the importance of incorporating both linguistic and social elements into teaching resources, promoting inclusivity and a supportive learning environment. The theoretical framework is grounded in Intercultural Communicative Competence (ICC), emphasizing the role of cultural awareness and identity in language learning. The results suggest that integrating tolerance dimensions into reading materials can enhance learning outcomes for heterogeneous EFL students, aligning with prior studies showing the positive impact of culturally diverse materials on student interaction and language development.